2020
DOI: 10.1002/adom.201902161
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan‐Induced Emissive J‐Aggregate Formation in a meso‐Ester BODIPY Dye

Abstract: The analyte‐directed formation of emissive J‐aggregates of a meso‐ester BODIPY dye is explored in the design of fluorescence “light‐up” probes. The heparin‐specific pyridinium‐functionalized meso‐ester BODIPY dye C10‐Py+ self‐assembles in aqueous buffer into spherical aggregated nanostructures with spectroscopic features indistinguishable from the monomeric dye (signal off). In the presence of heparin, the aggregated assemblies rearrange and associate with heparin through charge‐pairing interactions, triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…(Reprinted with permission. [ 26 ] Copyright 2020, Wiley‐VCH). (D) Fluorescence spectra of 7 resulted by the addition of various metal ions to the compound were depicted.…”
Section: Photophysical Property Changes Of Conventional Fluorophore A...mentioning
confidence: 99%
See 3 more Smart Citations
“…(Reprinted with permission. [ 26 ] Copyright 2020, Wiley‐VCH). (D) Fluorescence spectra of 7 resulted by the addition of various metal ions to the compound were depicted.…”
Section: Photophysical Property Changes Of Conventional Fluorophore A...mentioning
confidence: 99%
“…The interaction with heparin, however, disrupted these spherical aggregates to J‐aggregated supramolecular assemblies, and it associated a high turn‐on response with specific interactions. [ 26 ]…”
Section: Photophysical Property Changes Of Conventional Fluorophore A...mentioning
confidence: 99%
See 2 more Smart Citations
“…The dramatic changes in spectral characteristics of the organic pigments from the monomeric to the aggregated form provide the basis for effective biosensing where the dye specifically interacts with the target molecules and convert from a fluorescence-quenched state to a fluorescence-active state to achieve fluorescence enhancement. These dye-aggregate probes have been investigated to selectively detect small molecules [ 46 , 47 ], proteins [ 48 ], DNA [ 49 ], and glycosaminoglycans [ 50 ]. One example demonstrated that an amphiphilic dicyanovinyl squaraine SQgl [ 49 ] could serve as a highly selective probe to detect G-quadruplexes (G4) in the parallel configuration (Fig.…”
Section: Utilization Of Dye Aggregates For Biomedical Applicationsmentioning
confidence: 99%